Serum vitamin B12 and related 5-methyltetrahydrofolate-homocysteine methyltransferase reductase and cubilin genotypes predict neural outcomes across the Alzheimerʼs disease spectrum. Issue 2 (17th March 2020) - McLimans, K. E.; Collazo Martinez, A. D.; Mochel, J. P.; Allenspach, K.; Willette, A. A.
Abstract: Epidemiological studies show mixed findings for serum vitamin B12 (B12 ) and both cognitive and regional volume outcomes. No studies to date have comprehensively examined, in non-supplemented individuals, serum B12 level associations with neurodegeneration, hypometabolism and cognition across the Alzheimerʼs disease (AD) spectrum. Serum B12 was assayed from the Alzheimerʼs Disease Neuroimaging Initiative (ADNI) and the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL). Voxel-wise analyses regressed B12 levels against regional grey matter (GM) volume and glucose metabolism ( P < 0·05, family-wise corrected). For ADNI GM, there were thirty-nine cognitively normal (CN), seventy-three mild cognitive impairment (MCI) and thirty-one AD participants. For AIBL GM, there were 311 CN, fifty-nine MCI and thirty-one AD participants. Covariates were age, sex, baseline diagnosis, APOE4 status and BMI. In ADNI, higher B12 was negatively associated with GM in the right precuneus and bilateral frontal gyri. When diagnostic groups were examined separately, only participants with MCI, or above an established cut-off for cerebrospinal fluid (CSF) total tau showed such associations. In AIBL, higher B12 was associated with more GM in the right amygdala and right superior temporal pole, which largely seemed to be driven by CN participants that constituted most of the sample. Our results suggest that B12 may show different patterns of association based on clinical status and, for ADNI, AD CSF biomarkers. Accounting for these factors may clarify the relationship between B12 with neural outcomes in late-life.